HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH DI KOTA JAKARTA SELATAN - Ressa Andriyani Utami; Ria Efkelin Mose; Martini Martini; Ary Rahmaningsih (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2020)
Background. School-age children who are the next generation are among the groups that are vulnerable to Covid-19, the cases of children confirmed positive for Covid-19 in Indonesia are still very high at around 7.2%. The Aim of The Study. Knowing the relationship between knowledge and Covid 19 prevention behavior in school-age children in South Jakarta. Subjects and Methods. This study used an observational analytic method with a correlational design. The subjects of this study were elementary school children in grades 4 to 6, the sample was taken using the cluster random sampling method. Data analysis using Pearson Correlation. Results. The majority of respondents have good knowledge, which is 58% and the majority of respondents have poor behavior in preventing Covid-19, which is as much as 78%. There is a relationship between knowledge and Covid-19 prevention behavior in school-age children (p = 0.001). Conclusion. There is a relationship between knowledge and Covid-19 prevention behavior in school-age children in South Jakarta. Keywords: covid-19, knowledge, prevention behavior in school age children Korespondensi: Ressa Andriyani Utami, Sekolah Tinggi Ilmu Kesehatan RS Husada, Jalan Mangga Besar Raya 137-139, Jakarta Pusat, DKI Jakarta. 11730. Email: ressa.andriyani.utami@gmail.com